A sharp floristic discontinuity revealed by the biogeographic regionalization of African savannas. (18th December 2018) - Fayolle, Adeline; Swaine, Michael D.; Aleman, Julie; Azihou, Akomian F.; Bauman, David; te Beest, Mariska; Chidumayo, Emmanuel N.; Cromsigt, Joris P. G. M.; Dessard, Hélène; Finckh, Manfred; Gonçalves, Francisco Maiato P.; Gillet, Jean‐Francois; et al.
Abstract: Aim: In tropical Africa, savannas cover huge areas, have high plant species richness and are considered as a major natural resource for most countries. There is, however, little information available on their floristics and biogeography at the continental scale, despite the importance of such information for our understanding of the drivers of species diversity at various scales and for effective conservation and management. Here, we collated and analysed floristic data from across the continent in order to propose a biogeographical regionalization for African savannas. Location: We collated floristic information (specifically woody species lists) for 298 samples of savanna vegetation across Africa, extending from 18° N to 33° S and from 17° W to 48° E. Taxa: We focused on native woody species. Methods: We used ordination and clustering to identify the floristic discontinuities and gradual transitions across African savannas. Floristic relationships, specificity and turnover, within and between floristic clusters, were analysed using a (dis‐)similarity‐based approach. Results: We identified eight floristic clusters across African savannas which in turn were grouped into two larger macro‐units. Ordinations at species and genus levels showed a clear differentiation in woody species composition between the North/West macro‐unit and the South/East macro‐unit. This floristic discontinuity matches to the High (i.e. N&W) and Low (S&E) division of Africa previously proposed by White (1983 ) and which tracks climatic and topographical variation. In the N&W savannas, the floristic gradient determined by rainfall was partitioned into the Sudanian (drier) and Guinean (wetter) clusters. Within the highly heterogeneous S&E savannas and woodlands, six clusters were identified: Ugandan, Ethiopian, Mozambican, Zambezian, Namibian and South African. Main conclusions: The proposed pan‐African classification of savannas and woodlands might assist the development of coordinated management and conservation policies.